A Preliminary Study on the Induction of Somatic Embryogenesis of Eusideroxylonzwageri Tesym and Binned (Borneo Ironwood) from Leaf Explant - Gibson, E.; Rebicca, E. (IJAIR, 2016)
Eusideroxylon zwageri is a tree of tropical rainforest zone and belongs to a Lauraceae family. It is one of the hardest timber species in Southeast Asia. The objective of this study was to determine the optimal culture medium for the induction of somatic embryogenesis f explants of E. zwageri. It was found that the globular somatic embryos were induced in half strength of MS medium with 1.0, 1.5, 2.0 mg/L of BAP in combination with either 0.5 mg/L of 2,4-D or NAA. The maturation of somatic embryos obtained in half strength of MS medium with BAP, NAA and GA3. The highest mean number of the induction of somatic embryos up to the cotyledonary phase was observed in culture medium containing 1.0 mg/L of BAP, 0.5 mg/L of NAA in combination with 1.0 mg/L of GA reported preliminary study was useful for further plantlet regeneration of this species through induction of somatic embryogenesis.